171 Staff perceptions of non-pharmacological interventions to manage delirium in the inpatient palliative care setting. Issue Volume 8: Issue (2018)Supplement 1 (1st March 2018) - Conway, Claire; Spiller, Juliet; Carduff, Emma; Finucane, Anne
Abstract : Background and aim: Delirium is a complex neuropsychiatric syndrome occurring in up to 88% of patients in palliative care inpatient settings in the weeks or hours preceding death. It is characterised by a disturbance in attention and awareness that develops over a short time and fluctuates in severity throughout the day. Management of a delirium episode includes the consideration of potentially treatable precipitating and aggravating factors followed by symptomatic treatment with drug therapy. A recent randomised clinical trial found no benefit of antipsychotic medication in the treatment of terminally ill patients, and called for an examination of the role of supportive interventions (Agar et al. 2017). The aim of the present study was to explore staff perspectives regarding supportive or non-pharmacological strategies to manage delirium in palliative care settings. Methods: Semi-structured interviews were conducted with nine members of the medical and nursing inpatient teams across two Scottish hospices. Interviews were transcribed verbatim and analysed thematically. Results: Most participants employed a mix of pharmacological and non-pharmacological approaches to treat delirium at the end of life. Non-pharmacological strategies included i) reorientation, ii) modifying environmental factors, iii) familiar surroundings, iv) enabling and retaining autonomy, v) distraction from delirium, and vi) tactile stimulation. Inadequate staffing was viewed as a barrier to the use of non-pharmacological interventions; whereas involving families in delirium management was viewed as helpful. Conclusion: A variety of non-pharmacological interventions were identified which were both commonly used and perceived to be effective by staff members in two palliative care inpatient units. An intervention study is now required to examine the effectiveness of supportive interventions to reduce delirium symptoms and severity in terminally ill patients, and to minimise delirium related distress in both the patient and their families.